Clinical effectiveness of diet therapy in preventing domestic cat obesity - Локес-Крупка, Т. П. (Scientific Progress & Innovations, 2018)
The purpose of the work is to determine the clinical effectiveness of diet therapy in case of domestic cat obesity. The cat’s owners addressed the veterinary clinic with complaints of labored breathing, periodic claudication, and defecatory disorders. Judging by the owner’s words, the cat practically did not move in the apartment, often slept, and rarely played. The animal was kept in a mixed diet. The weight of the animal was 7.3 kg, the general condition was depressed. The percentage of fat deposits was over 35 %, which confirmed obesity. Changes in the morphological analysis of blood were insignificant and not specific for differential diagnosis. Characteristic serological changes were: hyperproteinemia; hyperlipidemia; cholestasis syndrome. Liver and renal markers were within the physiological norm. The first step to improve the animal's condition was the recommendation to conduct diet correction and organize exercises. As diet therapy, “Royal Canin Satiety” was used for three months. It was also recommended to use probiotics and chondroitin with glucosamine for one month. For movement we recommended active games with the cat. During the subsequent visits, the decrease of body weight, fat deposits, and improvement of the quality of the cat's movements were observed. After three months of diet therapy, Lolla's weight was 5.2 kg, she became more playful, labored breathing was not recorded, the act of defecation normalized. Consequently, in order to ensure normal metabolism and eliminate the risk of developing obesity in domestic cats, the following measures are necessary: walks, balanced diet, no delicacies and scraps of food from the table, strict compliance with the frequency of feeding and the amount of finished feed.